Penerapan Brand Awareness dan E-Marketing pada Toko Natasyia Collection pada Situasi Pandemi COVID-19 - Lady Lady; Lisa Aini (Universitas Internasional Batam, 2021)
The development of technology makes e-marketing technology become an important marketing strategy because it is able to reach a wide community network. Moreover, brand awareness is also very important for any business because it is not only invites consumers to buy for the first time, but also makes consumers continue to buy the brands we have and if they are satisfied, they will most likely promote to other people about our brand and also it can survive and to be more advance for our business. The design of e-marketing and brand awareness in this study deals with micro, small and medium enterprises, namely Natasyia Collection store. The problem is there is no brand awareness yet and also still used the conventional marketing. But after the implementation activities, Natasyia Collection Store was able to reach a wider range of consumers and increased sales turnover for the last 3 months by marketing through social media, namely Instagram and Facebook and e-commerce, namely Tokopedia, making promotional videos, Linktree, e-content marketing and an interesting e-catalog. In addition, the creation of brand awareness by making brand logos, banners, clothes tags, thank you card and an interesting packaging. This research is a qualitative research using case studies. Data obtained through interviews, observation and documentation. In further research, it can develop marketing through social media and other e-commerce such as Whatsapp Bussiness, Tiktok, Shopee, Bukalapak and Lazada and can develop brand awareness with promotions that are even more interesting than the previous ones.